Taking the Stand: Access to Justice for Witnesses with Mental Disabilities in Sexual Assault Cases - Benedet, Janine (2012)
In this article the authors argue that the existing adversarial trial process often prevents the stories of sexual assault complainants with mental disabilities from being heard in court. Relying on social science evidence, the authors argue that subjecting a woman with a mental disability to a rigorous cross-examination with repeated and leading questions, in a manner that is confrontational and often accusatory, is probably the worst way to get her story heard accurately in court. It is likely to unfairly undermine her credibility and to result in unjustified acquittals or in prosecutors deciding not to pursue a case. The article examines the challenges posed by traditional methods of cross-examination for witnesses with cognitive, developmental, or intellectual disabilities that affect their ability to recall, process, and communicate information, suggesting that existing Criminal Code accommodations are inadequate to address these concerns. Cross-examination should be conducted in a way that respects both the right of the accused to a fair trial and the complainant’s right to sex equality. Relying on developments in other jurisdictions, the authors recommend adopting a system of victim support persons or intermediaries, which would allow witnesses with mental disabilities to have assistance in understanding questions and in communicating their evidence to the court as fully as possible. Judges should also be given explicit legislative authority to intervene to disallow questions that are inappropriate based on the particular witness’s abilities. Such accommodations facilitate rather than impede the truth-seeking function of a trial and are not inconsistent with the fair trial rights of the accused